Deferasirox therapy is associated with reduced mortality risk in a medicare population with myelodysplastic syndromes. (August 2015) - Zeidan, Amer M; Hendrick, Franklin; Friedmann, Erika; Baer, Maria R; Gore, Steven D; Sasane, Medha; Paley, Carole; Davidoff, Amy J
Aims: Iron overload adversely affects patients with myelodysplastic syndromes (MDS), but benefits of iron chelation therapy have not been clearly demonstrated. We examined the association between deferasirox (DFX) therapy and mortality in transfusion-receiving Medicare patients.Patients & methods: MDS patients from 2005 to 2008 were identified using ICD-9 codes from 100% Medicare claims. Patients receiving ≥20 blood units were observed until death or end of study. Marginal structural models were used for estimation.Results: 3926 patients (10.1% used DFX) were observed for a mean of 48.8 weeks. Each incremental week of DFX was associated with a significant reduction in mortality risk (hazard ratio [HR]: 0.989; 95% CI: 0.983–0.996; p = 0.001).Conclusion: DFX therapy is associated with a reduced mortality risk among older MDS patients who received a minimum transfusion threshold.